Group portrait of sixteen people - Victory Studios, VS; Kilkenny Association, KILK
Colour group portrait photograph of sixteen people, some partly hidden behind others. Mounted in a 'Mecca Banqueting Halls' card folder. Photograph by Victory Studios, copyright Victory Studios.